Pengaruh Media Tanam terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L.) secara Hidroponik - Sri Anggriyanti Putri Bohoka; Jusna K. Ahmad; Syam S. Kumaji (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the effect of the combination of planting media of sorghum dregs compost and husk charcoal on hydroponic growth of pakcoy plants and to determine the combination of planting media that gives the best effect on hydroponic growth of pakcoy plants. This research was conducted at the Gorontalo Agricultural Technology Study Center with the research time starting from July to September 2021. The research method used was the experimental method. Pakcoy seedlings were sown on planting media with a combination of sorghum dregs compost and husk charcoal, then transferred to the NFT system hydroponic pipe installation at 14 days after planting. The results showed that the planting medium had an effect on the growth of pakcoy plants. Based on the results of 5% BNT, it was found that the combination of 50% sorghum dregs compost and 50% husk charcoal (M4) had a significant effect on the growth of pakcoy plants which included plant height, leaf length, leaf width and plant wet weight. The combination of planting media of 50% sorghum dregs compost and 50% husk charcoal (M4) had a significant effect on plant height and leaf number of pakcoy plants. While the combination of planting media with 25% sorghum pulp compost and 75% husk charcoal (M5) had a significant effect on leaf length, leaf width, dry weight and wet weight of pakcoy plants